(3JaSjQ GdELQGAGJ GdLfGFjI aj VhA bhGYO CUhd Gdabg (B:s (3fTCI GdJaSjQ hCgejJg hWHjYJg heOGQSg hfXQjGJg GdJaSjQ GddZhj hGdefWbj hGdZGfj(B-(3GdJaSjQ GdJTQjYj hGdbVGFj hGdabg hGdeVjb hGdehSY(B-(3GdbjGS(B-(3GdfSN (B/s - (3aGQhb, jGSQ GdCejQs ((3GdbGgQI (B:s (3OGQ GdfgVI GdYQHjI ddfTQ hGdJhRjY,s, 2015)
(3jJfGhd cJGH (B((3JaSjQ GdELQGAGJ GdLfGFjI aj VhA bhGYO CUhd Gdabg (B: (3fTCI GdJaSjQ hCgejJg hWHjYJg heOGQSg hfXQjGJg GdJaSjQ GddZhj hGdefWbj hGdZGfj(B-(3GdJaSjQ GdJTQjYj hGdbVGFj hGdabg hGdeVjb hGdehSY(B-(3GdbjGS(B-(3GdfSN(B) (3hGdPj bGe HJCdjag (B((3jGSQ GdCejQ aGQhb(B) (3aj MhGdj (B(635) (3UaMI ef GdbWY GdeJhSW ehVhY (B((3bGfhf GdELQGAGJ GdLfGFjI(B) (3eSJYQVG CHQR GdeMJhjGJ GdJGdjI (B: (3GdHGH GdJegjOj (B: (3GdeONd dOQGSI GdJaSjQ(B... (3EdN(B.s
(3jTJed Ydi EQLGYGJ HHdjhLQGajI(B.s
Keywords: (3bGfhf GdELQGAGJ GdLfGFjIs; (3GdLfGjGJ (B((3abg ESdGej(B)s